Internet of Things and Supply Chain Management: An Empirical Analysis of Nigeria Perspective - O. Omotayo, Olota; Iortimbir, Aun I.; Oluwadamilare, Balogun E. (Journal of Techno-Social, 2023)
IT developments is a paradigm shift in various domains, including supply chain management (SCM). This study examines internet of a thing (IOT) and SCM; an empirical analysis of Nigeria perspective. The study examined IOT factors and its effect on SCM, with a specific focus on Jumia Nigeria. The survey research design was used in this study. The study’s sample size is comprised of 265 members of Jumia employees who were randomly selected with 253 valid responses retrieved. SmartPLS3 was used for the analysis, and hypotheses were tested using structural equation model at a significance threshold of 0.05 to see whether they were correct. Results demonstrated that IOT has a standardized beta value and P value of 0.948 and 0.000 on SCM which its r2 indicates 89.9% on SCM. In conclusion, IOT factors integration will lead to continuous improvement as it helps to enhanced its supply chain management.